Characterization of CrMoBW-Fe base in-flight particles and splats fabricated by nano-structured cored wire arc spraying - Man Tuiprae (2018)
© Copyright 2017 by DVS Media GmbH. All rights reserved. Properties and performance of the coating fabricated by wire arc spray process strongly depend on various factors including spray parameters and characteristics of both in-flight particle and splat. In this study, relationship between in-flight particle, splat formation and microstructure of the CrMoBW-Fe based nanocomposite coating fabricated by wire arc spray process were investigated. The Focus ion beam (FIB) milling was used to prepare a transversal cross-section of the in-flight particle and splat to be characterized by scanning electron microscopy (SEM) along with an energy dispersive x-ray spectroscopy (SEM-EDS). In addition, phase compositions were also analyzed by using x-ray diffractometer (XRD). The results revealed that size of the in-flight particles and splat morphology greatly influenced microstructure and properties of the coatings. In-flight particles were revealed a spherical-shape with a broad size distribution ranging from 0.8 to 115 μm at the average of 26 μm particle diameter. In-flight particles were well flattened on impact giving flower-shape splat with the average diameter of 100 urn. Flattening degree was found to be 3.8. Arc sprayed CrMoBW-Fe base nanocomposite coating showed very thin splat with fine lamella structure which implied that particles were fully molten upon impact onto substrate.